ANALISIS SEMIOTIKA PESAN DAKWAH DALAM FILM JEJAK LANGKAH 2 ULAMA KARYA INISIASI KH. SALAHUDDIN WAHID - Khoir, Syabikul; Masruroh, Sayyidah Afyatul (Universitas Hasyim Asy'ari, 2023)
Along with the times, preachers realized that the role of film as an educational medium is very influential for people's lives. Therefore, preachers also use film as a medium of da'wah, to build the character of an Islamic Muslim community. The film Traces of Steps 2 Ulama (JL2U), directed by Sigit Ariansyah produced by the Tebuireng Production House (MAKSI) and Mix Pro Yogyakarta, tells the story of the life journey of 2 major figures in Islamic da'wah in Indonesia, namely KH. Hasyim Asy'ari and KH. Ahmad Dahlan. This film was the result of negotiations and collaboration between the Muhammadiyyah Cultural Arts and Sports Institute (LSBO) and the Tebuireng Islamic Boarding School under the auspices of Gus Sholah at that time. This study aims to analyze the signs and meanings of the da'wah message signs in the film, namely the da'wah messages of aqidah, sharia and morals. The message of aqidah da'wah conveyed in this film is about faith in God, faith in God's books, and God's messengers. The sharia da'wah messages conveyed are about worship and muamalah, namely the order to ask questions to those who are more expert, the order to love fellow beings, perform the pilgrimage, teach knowledge, the order to help each other, the order to leave sins, the order to advise in patience, and the order to forgive each other . The message of moral da'wah conveyed in this film is about wisdom, humility and obedience to teachers, helping fellow human beings, reminding each other, and patience and sincerity.